GOOGLE AND LIBRARY CONTESTATION IN READING CULTURE IN FACULTY OF SOCIAL AND POLITICAL SCIENCES, UDAYANA UNIVERSITY - Suhartika, I Putu (International Conference on Cultural Studies, 2018)
Reading is a cognitive process for obtaining information used as a response of uncertainties. Today, information can not only be obtained through printed media like books in libraries, but also through online media with search engines like Google. The presence of such information media strongly supports reading culture. This research focuses on the contestation of Google and Library in the university. The contestation will describe user perception to the existence of Google and Library as information institution. The method of the research is qualitative method. The result of the research will be then analyzed by critical theories. The results showed that 87% of informants choose Google, and 13% choose Library as tool of information retrieval. The reasons why they choose Google are all information available, open system, effective, efficient, modern, cost, and easy access. They choose Library because of relevant, accurate and selected information. The result also showed that globalization is able to make library access easier, and raise global products in the local context of the community. Besides this, the main discourse of “Google” brings up new discourses in the field of libraries such as electronic or digital library.